2020
DOI: 10.1016/j.ctarc.2020.100210
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted magnolol inhibits OXPHOS, proliferation, and tumor growth via modulation of energetics and autophagy in melanoma cells

Abstract: Introduction: Melanoma is an aggressive form of skin cancer for which there are no effective drugs for prolonged treatment. The existing kinase inhibitor antiglycolytic drugs (B-Raf serine/threonine kinase or BRAF inhibitors) are effective for a short time followed by a rapid onset of drug resistance. Presentation of case: Here, we show that a mitochondria-targeted analog of magnolol, Mito-magnolol (Mito-MGN), inhibits oxidative phosphorylation (OXPHOS) and proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 72 publications
(133 reference statements)
2
30
0
Order By: Relevance
“…Consistent with Mito-MGN inhibiting melanoma growth in vitro , Ki-67 immunostaining indicated a marked reduction in cell proliferation of Mito-MGN treated melanomas in vivo ( Figure 1 H). These anti-tumor effects of Mito-MGN in murine melanoma agree with our recent report in human melanoma cells and xenografts ( Cheng et al., 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with Mito-MGN inhibiting melanoma growth in vitro , Ki-67 immunostaining indicated a marked reduction in cell proliferation of Mito-MGN treated melanomas in vivo ( Figure 1 H). These anti-tumor effects of Mito-MGN in murine melanoma agree with our recent report in human melanoma cells and xenografts ( Cheng et al., 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…Further, T cells may possess a more hyperpolarized mitochondrial membrane potential, suggesting those cells may also be targeted by TPP-conjugated compounds ( Sukumar et al., 2016 ). Here, we show that targeted inhibition of complex-I using Mito-MGN ( Cheng et al., 2020 ) has tumor intrinsic and tumor extrinsic immune remodeling effects in an immune competent mouse model. Moreover, direct treatment of Mito-MGN stimulated the concomitant inhibition of melanoma proliferation with the proliferation-independent activation of T cells and inhibition of MDSC within tumors.…”
Section: Introductionmentioning
confidence: 94%
“…It is an important challenge to find effective and economic antitumor drugs with minimum side effects. A large number of literature studies have shown that MG has antitumor activity against colon cancer (Kang et al, 2012;Park et al, 2012), prostate cancer , liver cancer, lung cancer (Seo et al, 2011;Shen et al, 2017), gastric cancer (Rasul et al, 2012), cholangiocarcinoma (Zhang FH et al, 2017), oral cancer (Hsieh et al, 2018), ovarian cancer (Chuang et al, 2011), breast cancer (Liu et al, 2013), and melanoma (Cheng et al, 2020). MG suppressed the growth, migration, and invasion of tumor cells and promoted apoptosis as well as autophagy by acting on caspase-8, caspase-3, and other proteins participated in the p53, MAPK, NF-κB, TLR, HIF-1α/VEGF, PI3K/Akt/ERK/ mammalian target of rapamycin (mTOR), and Wnt/β-catenin signaling pathways (Chen et al, 2013;Liu et al, 2013;Li et al, 2015;Shen et al, 2017;Zhang P et al, 2017).…”
Section: Antitumor Activitymentioning
confidence: 99%
“…We have not yet investigated the tumor regressing effects of Mito-HUs in an in vivo mouse model. However, we have previously shown that mitochondria-targeted drugs cause regression of tumors in mice xenografts (Cheng et al, 2013(Cheng et al, , 2016(Cheng et al, , 2020bBoyle et al, 2018). To fully understand the antitumor immune mechanism of Mito-HU in an in vivo setting, it is essential to perform studies in immune-competent mice.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Later, HU was shown to be effective against myeloproliferative disorders, CML, and polycythemia rubra vera (Spivak and Hasselbalch, 2011). It was also postulated that HU could stimulate an immune response in melanoma and lung cancer by recruiting components of the innate immune system (Cheng et al, 2020b;Oo et al, 2019). Typically, high concentrations of HU are required for in vitro and in vivo efficacy in chemotherapy (Singh and Xu, 2016).…”
Section: Introductionmentioning
confidence: 99%